2016
DOI: 10.3384/lic.diva-131623
|View full text |Cite
|
Sign up to set email alerts
|

Driving in Virtual Reality: Investigations in Effects of Latency and Level of Virtuality

Abstract: When developing new active safety systems or improving existing systems, conducting performance evaluations is necessary. By performing these evaluations during early development stages, potential problems can be identified and mitigated before the system moves into the production phase.Testing active safety systems can be difficult since the characteristic scenarios may have complex interactions. Using real vehicles for performing these types of scenarios is difficult, expensive, and potentially dangerous. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…200°in the real world [23]), potentially reducing optic flow, while peripheral information is available with other displays. We also found that many research papers on HMDs are comparatively old or used low-fidelity HMDs, which is often associated with lower resolution [8], contrast, FOV, etc. Thus, the differences found between HMDs and other displays may also be attributed to other hardware properties.…”
Section: A Display Technologies In Driving Simulatorsmentioning
confidence: 68%
See 1 more Smart Citation
“…200°in the real world [23]), potentially reducing optic flow, while peripheral information is available with other displays. We also found that many research papers on HMDs are comparatively old or used low-fidelity HMDs, which is often associated with lower resolution [8], contrast, FOV, etc. Thus, the differences found between HMDs and other displays may also be attributed to other hardware properties.…”
Section: A Display Technologies In Driving Simulatorsmentioning
confidence: 68%
“…HMDs offer a cheap solution as all elements of a real vehicle can be displayed virtually, hence no physical mockup is required. [8] proposed that 40 % of the studies could be conducted using HMDs. They mention as a benefit that HMDs are, at least partially, able to provide binocular depth cues.…”
Section: A Display Technologies In Driving Simulatorsmentioning
confidence: 99%
“…A driving simulator commonly has a design in between these extremes. Vehicle hardware is also commonly included to various degrees, ranging from simple driver controls to a complete car where techniques such as augmented reality may be explored (Blissing 2016). The focus in this work are human drivers in a high fidelity moving base driving simulator.…”
Section: Driving Simulatorsmentioning
confidence: 99%
“…When virtual objects are added to the real world, mainly is used the term "augmented reality" (AR). A typical example of AR is to add annotations to objects in the real world, but it can also be to add a virtual object to the real world, such as a virtual teapot placed on a real table or a virtual vehicle in a real traffic environment or a virtual singer from the past on a stage that stands next to a modern star (Blissing, 2016). On this continuum is also (more uncommon) augmented virtuality (AV), which means to add real objects to an otherwise virtual world.…”
Section: Introductionmentioning
confidence: 99%